ANALYSIS OF TEUN'S DISCOURSE A. VAN DIJK IN TELLING THE PEOPLE'S MIND "ELECTION OF UNPAD RECTORS: OMBUDSMAN DISCOVER TWO MALAADMINISTRATION" - Abdul Azis Muslim; Mochamad Supriyadi; Ika Mustika (JLER (Journal of Language Education Research), 2020)
This study discusses reporting on "Election of Unpad Rector: Ombudsman Finds Two Maladministration" in print media. The background of this research is the alleged alignment of the daily Pikiran Rakyat daily newspaper in publishing news. The aim of this research is to find the position of Pikiran Rakyat's daily newspaper on the news of Unpad Rector Election: Ombudsman Finds Two Maladministration. Researchers began to analyze the news Unpad Chancellor Election: Ombudsman Discovered Two Malala Administration which was published in the Daily Mind newspaper on October 26, 2018 based on the theory of Teun A. Van Dijk. This study uses qualitative research methods and analysis with Teun A. Van Dijk's critical discourse analysis model based on several elements of discourse structure: Macro Structure, Super Structure, and Micro Structure. After analyzing the discourse, the researchers found that the print media of the People's Mind was neutral in a report entitled Unpad Rector Election: Ombudsman Finds Two Maladministration. The facts displayed in the media are only involved in the reporting process.